The Rising Tendency of Migration Among Young Generation and its Impact on the Bangladeshi Economy - Aktar, Ayesha; Islam, Md. Saiful; Uddin, Kazi Mohammed Kamal (ESI Preprints (European Scientific Journal, ESJ), 2025)
This study investigates the rising tendency of migration among the young generation in Bangladesh and its perceived impact on the national economy. Drawing upon the Push-Pull Theory (Lee, 1966) and the Theory of Planned Behavior (Ajzen, 1991), the research examines how push factors (e.g., political instability, job scarcity), pull factors (e.g., better salaries, residency prospects), and financial feasibility influence students’ intention to migrate. Data were collected from 250 university students through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that pull factors exert a stronger influence on migration intention than push factors, suggesting aspirational migration driven by global opportunities rather than merely escaping domestic constraints. Financial feasibility partially mediates the impact of push/pull factors, confirming the role of economic access in migration decisions (Stark, 1991). Interestingly, government policy perception does not significantly moderate migration intention, highlighting a gap between policy initiatives and youth trust or awareness (Siddiqui, 2020). Moreover, migration intention shows a negative correlation with perceived economic impact, reflecting student concerns about brain drain despite recognizing the benefits of remittances (Docquier & Rapoport, 2012). The study recommends reforms in employment, education, and diaspora engagement policies to address migration drivers while harnessing its developmental potential. These insights contribute to the discourse on youth mobility and economic sustainability in emerging economies like Bangladesh.